Unlocking reading skills (maharah qira’ah) mastery: An engaging analysis of Ma’āyīr Mahārāt al-Lughah al-’Arabiyyah lil Ghairi Nāthiqīn bihā - Saadah, Badriyyah; Baroroh, R. Umi (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2025)
This study explores effective strategies for teaching maharah qira’ah (reading skills) to non-Arabic speakers, focusing on an analysis of the book Ma’āyīr Mahārāt al-Lughah al-’Arabiyyah lil Ghairi Nāthiqīn bihā. The research aims to identify and analyze various effective strategies in maharah qira’ah instruction. The primary objective is to propose alternative strategies that can enhance students' maharah qira’ah proficiency. This study employs a qualitative method with a descriptive-analytical approach through literature review. The main data source is the book Ma’āyīr Mahārāt al-Lughah al-’Arabiyyah lil Ghairi Nāthiqīn bihā, supplemented by relevant scholarly literature. The findings reveal that effective strategies for maharah qira’ah instruction include the phonetic approach, vocabulary development, contextual comprehension, repeated and rapid reading techniques, and the integration of learning technologies. The study emphasizes the importance of selecting appropriate strategies to address challenges in maharah qira’ah and support successful Arabic language learning.